Difficulties That Face BA Students When Translating Prepositions of Movement from English into Standard Arabic - Dawoud, Nadia Lutfi Dawoud; Al Hanaqtah, Mohammed (عمان, 2017)
There are skills that students must have to be able to translate. The study aims to discover the difficulties that face BA students when translating prepositions of movement from English into Arabic and to know who has the higher proficiency males or females. The study also aims to discover the appropriate translation techniques students can use in translating from the experts' perspective who are university instructors. The study sample consisted of 60 students (30 males and 30 females) randomly chosen who are majoring in English and translation and who have completed at least one course in translation selected from three private universities in Jordan. In order to achieve the objectives of the study, the researcher used two instruments: a translation test consisted of 30-statements applied to the sample of study and a questionnaire applied to 30 experts from public and private universities. The results of the two instruments showed that students encountered difficulties in translating the prepositions of movement associated to lack of competence in students' language, in English and in Arabic which is the mother tongue. Also associated to their humble experience in translation, to their unfamiliarity of the movement prepositions and to their failure to translate these prepositions correctly into the nearest equivalent in Arabic. In addition to grammatical, syntactical and semantic difficulties. Results revealed that the use of the communicative translation is one of the most successful techniques in translation. Motivating students to practice translating prepositions of movement in lectures through continuing exercises is a procedure which scored the highest percentage in the experts' questionnaire.
Keywords: طلبة البكالوريوس -- الترجمة -- حروف الجر -- اللغة الإنجليزية -- اللغة العربية الفصحى